Neutrophil gelatinase-associated lipocalin (NGAL) for the early detection of cardiac surgery associated acute kidney injury. (August 2013) - Liebetrau, Christoph; Dörr, Oliver; Baumgarten, Heike; Gaede, Luise; Szardien, Sebastian; Blumenstein, Johannes; Rolf, Andreas; Möllmann, Helge; Hamm, Christian; Walther, Thomas; Nef, Holger; Weber, Michael
Abstract Background. Acute kidney injury (AKI) is a common complication after cardiac surgery. Neutrophil gelatinase-associated lipocalin (NGAL) may be an early biomarker for cardiac surgery–associated (CSA) AKI. We investigated whether increased urinary NGAL concentrations were predictive of AKI within 4 days after surgery and of mortality within 9 months. Methods. Consecutive patients (n = 141) undergoing major cardiac surgery were included. Creatinine, blood urea nitrogen, cystatin C and urinary NGAL were measured before, 4 hours and 4 days after extracorporeal circulation. Results. AKI was observed in 47 (33.3%) patients. The 4-hour urinary NGAL measurement was an independent predictor of stage 2 and 3 AKI (AUC 0.901; 95% CI 0.81–0.99). Patients with AKI had a higher 9-month mortality rate (19.1% vs. 3.2%; logrank 10.9; P = 0.001; HR 19.8; 95% CI 3.7–107.1). Urinary NGAL was not predictive of mortality within 9 months after surgery. Conclusion. Urinary NGAL is a biomarker for very early risk stratification of AKI after cardiac surgery and may be useful as a basis for early interventional strategies to prevent CSA-AKI.